Скульптурне оздоблення пресвітерії готичного кафедрального собору у Вроцлаві. Проблема зорових ілюзій - Юрковлянець, Т. (Студії мистецтвознавчі, 2008)
In the chancel of the Cathedral of St. John the Baptist (ca. 1244–1265?) in Wrocław the number of architectural elements as well as the selection of their decoration motifs follow the rules of the calendar. However, the purpose of the chancel decoration is not the calculation of time. One of the functions of mediaeval art was to «recall the life of our predecessors». In antiquity a distinction was made between natural and artificial memory which consists of places (locus) and images (imago). The recommendation for loci was to use interiors and architectural elements of buildings. Imagines where sings or effigies of what we wanted to retain in memory. According to Sicardus of Cremona church decoration was to remind of the past things and show the present and future ones. While viewing the presentation on the capital [15 – two human figures and an ape; figs. 6, 7], on the seventh from the west wall abutment in the northern aisle, one experiences an optical illusion (spontaneously experienced by the scholars studying the Cathedral). Depending on the view point (viewed either from south-west or south-east) one perceives two different scenes. They can be interpreted as a presentation of miracles (saving of the Wrocław castle by Prior Czesław OP; finding of the corpse of St. Hedwig’s son), which took place in Silesia during the Mongol invasion in 1241 (7 being the golden ratio).